Natural antifungals for managing black spot disease in papaya: Efficacy of essential oils and bioactive compounds against Asperisporium caricae - Adilson Vidal Costa; Maria Laura Urbano Nascimento; Lais Oliveira Rodrigues; Mariana Belizario de Oliveira; Walter Cesar Celeri Bigui; Poliana Aparecida Rodrigues Gazolla; Matheus Ricardo da Rocha; Willian Bucker Morais; Juliana Alves Resende; Gabriel Jacomin Vargas da Silva; Róbson Ricardo Teixeira; Vagner Tebaldi Queiróz; et al. (Postharvest Biology and Technology, 2026)

Advances in ELISA-based detection of equine leptospirosis - Thayná Laner Cardoso; Daniela Rodriguero Wozeak; Isabel Ladeira Pereira; Laura Dias da Silva Ribeiro; Rogério Oliveira Rodrigues; Daiane Drawanz Hartwig (Brazilian Journal of Microbiology, 2026)

An exploratory traffic impact analysis in a knowledge-based urban development area: the HIDS/UNICAMP case study - Vitor Eduardo Molina Junior; William Machado Emiliano; Vivian Silveira dos Santos Bardini; Marcela Noronha Pinto de Oliveira e Sousa; Silvia Regina Stuchi Cruz; Bruno Noronha Rodrigues; Ana Laura Fragoso Favoreti; José Telhada; Felippe Benavente Canteras (Clean Technologies and Environmental Policy, 2026)

Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Transboundary plastic pollution from North American lobster fisheries reaches Atlantic Islands - Christopher K. Pham; Dejalme Vargas; Valter Medeiros; João M. Pereira; Laura Herrera; Pedro Machado; Clara Rodrigues; Thomas Belaoud; Yasmina Rodríguez (Environmental Monitoring and Assessment, 2026)

Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.

Beyond Tubipora musica: Phylogenomics unveils the overlooked diversity and endemism of the hermatypic octocoral genus Tubipora - Laura Macrina; Tullia I. Terraneo; Catherine S. McFadden; Andrea Sabino; Nicolas Oury; Federica Barreca; Silvia Vicario; Kaveh Samimi-Namin; Daniel Knop; Mattie Rodrigue; Vincent Pieribone; Andrew H. Baird; et al. (Molecular Phylogenetics and Evolution, 2026)

Clonal Propagation of Khaya spp.: Epicormic Shoot Emission in Adult African Mahogany Species - Júlio Cézar Tannure Faria; Laura Ribeiro Atala; Cassia dos Santos Azevedo; Marcos Vinicius Winckler Caldeira; Tiago de Oliveira Godinho; Fatima Conceição Marquez Piña-Rodrigues (Forest Science, 2026)
Research on vegetative propagation in the genus Khaya remains limited and has focused mainly on juvenile trees, which restricts the selection of plus trees previously tested for growth potential and economic value. This study aimed to evaluate the vegetative propagation of three African mahogany species by inducing epicormic shoots in adult trees, and to investigate evidence of rejuvenation/reinvigoration during adventitious rooting, as well as the influence of branch diameter on bud and shoot emission. Plant material was collected from an experimental plantation using basal branches of 10-year-old trees. For each species, 72 leafless branches were standardized and maintained in a climate-controlled greenhouse. The experiment followed a completely randomized design with three diameter classes. After 21 days, the number of buds and shoots emitted per branch was recorded. Biochemical analyses included the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), total proteins, and total carbohydrates to characterize metabolic differences between adult tissues and epicormic shoots. Results indicate that branch diameter had a significant effect on bud and shoot emission in all three African mahogany species, with branches 4.5–6 cm in diameter being the most suitable source material. For assessing tissue rejuvenation and metabolism, SOD and CAT activities in K. senegalensis , SOD activity in K. grandifoliola , and total carbohydrate content in K. ivorensis were the most responsive biochemical variables for distinguishing epicormic shoots from adult tissues. Although adventitious rooting percentages were low, this study indicates that epicormic shoot induction in adult trees is a feasible strategy for obtaining vegetative propagules.

Mechanisms of dyspnoea and exercise intolerance in smokers with preserved ratio impaired spirometry - Alice Scussel; Nathalia Galvagni Rodrigues; Artur Zanelatto Santos; Laura Corrêa de Barros Trombin; Amanda Calage Pinto; Litiele Evelin Wagner; Marli Maria Knorst; James Dean; Dave Singh; Danilo Cortozi Berton (European Journal of Applied Physiology, 2026)
Purpose Smokers with preserved ratio impaired spirometry (PRISm) present reduced forced expiratory volume in the first second (FEV₁ < 80% predicted) but preserved FEV 1 /forced vital capacity (FVC) ≥ 0.7. Although they do not meet diagnostic criteria for chronic obstructive pulmonary disease (COPD), they often report respiratory symptoms and exercise intolerance. We aimed to compare sensory and physiological responses to exercise between smokers with PRISm and matched healthy controls. Patients with mild-to-moderate COPD were included as a reference group. Methods In this cross-sectional study, smokers (> 10 pack-years) from a specialized outpatient clinic were evaluated. Thirteen participants (11 females; 62.4 ± 7.7 years) with PRISm and 13 age- and sex-matched patients with mild-to-moderate COPD (FEV₁/FVC < 0.7; FEV₁ > 50% predicted) underwent incremental cardiopulmonary exercise testing on a cycle ergometer. Data from healthy nonsmoking controls were obtained from previous studies. Results PRISm and COPD groups had similarly reduced FEV₁ (~ 72% predicted) compared to controls (97% predicted), whereas FVC was lower in PRISm (73% predicted) than in COPD and controls (~ 95% predicted). Both patient groups showed higher ventilation, reduced ventilatory reserve, and greater dyspnoea at a given submaximal workload versus controls. Increased tidal volume/inspiratory capacity ratios were also observed, contributing to greater dyspnoea for a given ventilation and lower peak work rate (42 ± 16 vs. 68 ± 11 vs. 94 ± 17% predicted, respectively; all P < 0.05). Conclusion Smokers with PRISm exhibit increased dyspnoea and reduced exercise tolerance compared to healthy controls, largely driven by excessive ventilatory demand and reduced ventilatory capacity during submaximal exercise.

Genomic and epidemiological insights into a non-toxigenic Vibrio cholerae O1 Ogawa from an autochthonous case in Brazil - André Felipe Santos; Pedro Panzenhagen; Verônica Dias Gonçalves; Laura Fabiana Vieira do Amparo; Joyce Figueira Pereira de Souza; Maria Eduarda Moreira; Maria Luiza Paula Pereira; Emily Moraes Roges; Lucia Helena Berto; Dália dos Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Early-pregnancy exposure to air pollution and stillbirth in São Paulo, Brazil – results from the FetRisks case-control study - Rafael Buralli; Dario Ezequiel Elias; Cláudio Makoto Kanai; Lays Janaina Prazeres Marques; Osmara Alves dos Santos; Gizelton Pereira Alencar; Zilda Pereira da Silva; Gerusa Maria Figueiredo; Mara S. Hoshida; Laura Rodrigues; Rossana Pulcineli Vieira Francisco; Hillegonda Maria Dutilh Novaes; et al. (Air Quality, Atmosphere & Health, 2026)
Stillbirth remains a major public health concern, particularly in urban settings with persistent air pollution, while evidence remains limited in middle-income countries. This study aims to examine the association between prenatal exposure to fine particulate matter (PM2.5) PM2.5 and stillbirth in São Paulo, Brazil. Case-control study including 348 antepartum stillbirths and 419 live births recruited from 14 public hospitals. PM2.5 exposure was estimated using residential addresses linked to the nearest air quality monitoring station. We evaluated median PM2.5 levels during the first trimester of pregnancy and sustained higher PM2.5 exposure episodes (> 12.7 µg/m³ for ≥ 3 weeks). We explored the interaction between air pollution and maternal factors. Multiple logistic regression models were adjusted for maternal sociodemographics. All participants were exposed to PM2.5 concentrations substantially above the WHO Air Quality Guidelines. Sustained higher PM2.5 exposure was associated with higher odds of stillbirth (ORadj 1.51; 95% CI: 1.03–2.25) and showed a significant interaction with maternal age ≥ 35 years, increasing the odds of having a stillbirth (ratio of ORadj 2.55 [95% CI: 1.08–6.23]). Stillbirth was associated with episodes of sustained higher PM2.5 exposure in early pregnancy, in a context where all women experienced high pollutant levels. The coexistence of high baseline PM2.5 exposure and multiple maternal vulnerabilities underscore the need for integrated strategies addressing air quality, health equity, and perinatal care to reduce preventable stillbirths in highly polluted urban environments.

Clinical and non-clinical Escherichia coli from chickens reveal antimicrobial resistance patterns of one health concern - Marianna Rodrigues de Souza Campos; Thomas Salles Dias; Verônica Dias Gonçalves; Marcia Lima Festivo; Emily Moraes Roges; André Felipe das Mercês Santos; Pedro Henrique Nunes Panzenhagen; Laura Maria Andrade de Oliveira; Patrícia Carvalho de Sequeira; Dália dos Prazeres Rodrigues; Maria Helena Cosendey de Aquino (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Effects of dried distillers grains supplementation on intake, digestibility, metabolism, and performance of suckling beef calves on pasture - Edinael Rodrigues de Almeida; Johnnatan Castro Cabral Gonçalves; Jean Marcelo Albuquerque; Luanna Carla Coelho; Patrícia Siqueira Leite; Lilian Yukie Pacheco Toma; José Augusto Moura Godinho; Laura Ferrarez Ricardo; Julia Liliane Vieira; Cláudia Batista Sampaio; Edenio Detmann; Ériton Egídio Lisboa Valente; et al. (Tropical Animal Health and Production, 2026)
The supply of metabolizable nutrients to suckling beef calves on pasture can improve their performance, increasing weaning weight and productivity in cow–calf systems. The objective was to evaluate the effects of dried distillers grains (DDG) inclusion on intake, digestibility, metabolism, and performance of suckling beef calves grazing tropical pastures. Forty-eight Nellore calves, 120 ± 35 days of age and 135 ± 23.4 kg of body weight (BW), were used. During 117 days, calves received one of the following treatments under a creep-feeding strategy: mineral mixture only, provided ad libitum (CONTROL); or concentrate supplementation (SUP, 6 g/kg BW, containing 225 g/kg crude protein) with 0% (SUP0), 48.4% (SUP48), or 96.8% (SUP96) DDG inclusion. Concentrate supplementation increased intake of dry matter (DM), crude protein (CP), non-fibrous carbohydrates (NFC), total digestible nutrients (TDN), and the CP/digestible organic matter ratio ( P < 0.10). Digestibility of DM, CP, and NFC decreased linearly with increasing DDG inclusion. Serum glucose, insulin-like growth factor 1, and blood urea nitrogen concentrations were higher in calves on concentrate supplementation ( P < 0.10). Concentrate supplementation increased average daily gain, weaning BW, and ribeye area ( P < 0.10), with no differences related to DDG inclusion ( P > 0.10). Supplementation improves beef calves nutritional characteristics, metabolism and performance. Additionally, DDG can be included in supplements for suckling beef calves grazing tropical pastures, with potential to replace traditional feedstuffs such as corn and soybean meal, without negatively affecting performance and serum metabolism.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Oral nanoparticle-encapsulated enzyme replacement therapy for mucopolysaccharidosis type I (MPS-I): a proof of concept study - Jose-Victor Álvarez; Lluis Lis-Lopez; Daniel Rodrigues; Carmen Pena; Susana-Belén Bravo; Victoria Díaz-Tomé; Selene Cuello Rodríguez; Laura López-Valverde; Bruno-Kotska Rodiño-Janeiro; Cristóbal Colón; Asteria Luzardo-Álvarez; Maria-Jose de Castro; et al. (Drug Delivery and Translational Research, 2026)

Too close for comfort? Mesozooplankton dynamics in Marine Protected Areas adjacent to mining tailings on the southeastern Brazilian shelf - Bianca Salvador; Laura Rodrigues da Conceição; Renato David Ghisolfi; Mônica Souza Mendes; Tayná Rosa Martins Paiva; Valéria da Silva Quaresma; Daniel Rigo; Gustavo Martins Rocha; Paulo Sergio Salomon; Gabriel Harley Costa Santos; Priscila Teixeira-Amaral; Márcio Murilo Barboza Tenório; et al. (Marine Environmental Research, 2026)

Phosphorus fractionation in vineyard soils: Influence of cover crops and duration of cultivation - Ana Luiza Lima Marques; Allan Augusto Kokkonen; Bruno Ehle de Souza; Douglas Grando; Laura Silva Dunker; Lenon Cerentini; Marcos de Lima-Rodrigues; Jean Michel Moura-Bueno; Gustavo Brunetto (Geoderma Regional, 2026)

Modified citrus pectin modulates splenic immune responses and galectin expression following cisplatin treatment in Wistar rats - Diego Dias dos Santos; Artur Francisco da Silva Neto; Laura Santana de Chiara; Mab Pereira Corrêa; Gisela Rodrigues da Silva-Sasso; José Marcos Sanches; Rinaldo Florencio-Silva; Lila Missae Oyama; Cristiane Damas Gil (Journal of Molecular Histology, 2026)
Modified citrus pectin (MCP), a polysaccharide from citrus fruits, modulates galectin-3 (Gal-3) and immune responses. Although MCP exhibits notable immunomodulatory effects, its role in drug-induced splenic and systemic toxicity remains unexplored. This study investigated the effects of MCP modulation on splenic immune remodeling and galectin expression in a rat model of cisplatin-induced toxicity. Wistar rats were divided into four groups ( n = 5 animals/group): control (SHAM), MCP (100 mg/kg/day for 7 days), cisplatin (CIS, 10 mg/kg/day for 3 days), and MCP + CIS. Spleens were collected 6 h after the final cisplatin dose. Cisplatin induced splenic structural disorganization and selectively reduced nitric oxide levels without broadly affecting antioxidant enzymes. Cisplatin treatment was associated with increased CD3⁺ T cell labeling and enhanced tissue expression of Gal-1, -3, and − 9. MCP administration did not restore splenic architecture but promoted increased hemosiderin deposition in the red pulp, suggestive of enhanced erythrophagocytosis and altered iron handling, and markedly reduced CD3⁺ T cell immunoreactivity. MCP associated with cisplatin also reduced Gal-1 and Gal-3 levels and altered the relationship between galectins and splenic immune cell populations. Correlation analyses revealed positive associations between Gal-1, -3, and − 9 and CD68⁺ macrophages, as well as a selective association between Gal-3 and CD3⁺ T cells, exclusively in MCP + CIS animals. MCP does not mitigate cisplatin-induced splenic damage but alters immune cell distribution and galectin-related responses during cisplatin exposure.

Differential expression of sperm capacitation-associated microRNAs in fresh and cryopreserved bovine semen - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues Oliveira; Maíra Bianchi Rodrigues Alves; Cibele Maria Prado Zinni; Yulizabeth Daniela Pinto Rojas; Juliano Coelho da Silveira; Felipe Perecin; Eneiva Carla Carvalho Celeghini (Animal Reproduction Science, 2026)

Chemical preservatives for raw milk quality control: Mechanisms, efficacy, and safety review - Rodrigo Antonio Pivatto; Franciele Rampazzo Vancin; Laura Beatriz Rodrigues; Juarez Vicente (International Dairy Journal, 2026)

Diagnostic evaluation of a recombinant chimeric Sporothrix brasiliensis protein-based ELISA for serological detection of feline sporotrichosis - Débora Matilde de Almeida; Laura de Vargas Maiocchi; Natasha Rodrigues de Oliveira; Camila Moura de Lima; Martha Bravo Cruz Piñeiro; Gabriela Ladeira Sanzo; Tatiélen Hernandez Severo; Odir Antonio Dellagostin; Marcia de Oliveira Nobre; Sérgio Jorge (Research in Veterinary Science, 2026)

Origin, viability, and cell cycle status of seminal somatic cells for potential application in cattle cloning via nuclear transfer - Higor da Silva Ferreira; Gabriella Borba de Oliveira; Eduardo de Oliveira Sanguinet; Ana Laura da Silva Feijó; César Augusto Pinzón-Osorio; Verônica Rafaela Benvenutti; Louise Fontoura Köhler; Marianna Bertolini; Fernando Almeida-Souza; Felipe de Jesus Moraes Junior; David Driemeier; Ana Lúcia Abreu-Silva; et al. (Reproductive Biology, 2026)

Biostimulant Potential of Vitamins in Soybean Cultivation - Vitória Carolina Dantas Alves; Sebastião Ferreira de Lima; Eduardo Pradi Vendruscolo; Travis Wilson Witt; Arthur Renan Fernandes Nogueira; Laura Martins Ferreira; João Flávio Floriano Borges Gomides; Evelyn Rodrigues de Lacerda; Cassio de Castro Seron; Ana Paula Leite de Lima (International Journal of Plant Production, 2026)

Sexual dysfunction associated with selective serotonin reuptake inhibitors in adults with depression: a systematic review and meta-analysis - Sarah Dagostin Ferraz; Leonardo Kuyunga; Peterson Rech; Maria Laura Rodrigues Uggioni; Ana Claudia Rodrigues Candido; Valdemira Santina Dagostin; Fabio Rosa Silva; Tamy Colonetti; Antonio José Grande; Maria Inês da Rosa (European Journal of Clinical Pharmacology, 2026)
Objective To systematically evaluate the impact of SSRIs on sexual function in adults with depression compared to placebo through a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods A systematic search using the terms “sexual dysfunction” , “depression” and “antidepressant” was conducted in PubMed/MEDLINE, LILACS, Embase, and the Cochrane Library for RCTs published up to June 2025. No language restrictions were applied. Both dichotomous and continuous outcomes were analyzed with 95% confidence intervals using RevMan 5.4. The risk of bias in individual studies was assessed independently by two reviewers using the revised Cochrane Risk of Bias tool for randomized trials (RoB 2). Results Thirteen RCTs met inclusion criteria for qualitative synthesis and six were included in meta-analyses. SSRIs were significantly associated with increased risk of orgasmic dysfunction (RR = 3.28, (95% CI of 2.33 to 4.60, p < 0.00001; I² = 8%,) and reduced sexual satisfaction (RR = 1.21, (95% CI of 1.11 to 1.32, p = 0.0001, I² = 0%,). A non-significant trend toward decreased sexual desire was observed (RR = 1.40, 95% CI: 0.92–2.12, p = 0.12; I² = 54%,). No significant differences were detected in total CSFQ scores compared with placebo. Conclusion SSRI use is consistently associated with sexual dysfunction, particularly orgasmic dysfunction and reduced sexual satisfaction. The GRADE assessment indicated high to moderate certainty of evidence. Orgasmic dysfunction showed high certainty, with concerns limited to risk of bias. Sexual satisfaction, sexual desire disorders, and CSFQ total scores demonstrated moderate certainty, mainly due to risk-of-bias issues.

Evaluation of the stability of concentrate feed stored in metallic silos under farm conditions in Brazil - Tiago Bordin; Elisangela Vilas Boas; Pedro Henrique Ferreira da Silva; Luciane Maria Colla; Fernando Pilotto; Laura Beatriz Rodrigues (Journal of Consumer Protection and Food Safety, 2026)
Maintaining the nutritional quality of stored concentrates is crucial for the health and productivity of dairy herds, particularly in tropical climates where high temperatures can accelerate feed degradation. This study aimed to monitor the effects of temperature and humidity variations on the quality of pelleted concentrate feed in steel silos under real-world Brazilian farm conditions during 28-day storage. Three 4-ton steel silos containing concentrate feed for lactating cows were evaluated on a dairy farm in southern Brazil. Internal and external temperature and humidity were recorded continuously. Samples were collected weekly (D0-D28). They underwent bromatological, physicochemical, and microbiological analyses (vitamins A and D3, fatty acids, total aerobic count, and mold/yeast counts). Despite extreme conditions (50 °C, 90% relative humidity) in the steel silos, microbial counts remained stable. However, vitamins A and D3 decreased significantly (233 ± 12 to 132 ± 13.08 µg/100 g dry matter (DM) and 1,577 ± 74 to 929 ± 295 IU/kg DM, respectively; 15–20% loss), while other nutrients remained stable. While metallic silos effectively preserve the quality of bulk feed in the short term, significant thermosensitive nutrient losses occur under tropical conditions. Farmers should align storage durations with seasonal climate patterns and consider protective technologies for vitamins. The findings highlight the need for comparative studies of storage methods and practical solutions tailored to tropical dairy systems, where nutrient preservation directly impacts milk production economics.

Evaluation of the effects of hybrids of metronidazole and eugenol analogues as inhibitors of the Staphylococcus aureus NorA efflux pump: an in vitro and in silico analysis - Lucas dos Santos Sa; João Arthur de Oliveira Borges; Francisco Ruan Moreira da Silva Santos; Cicera Laura Roque Paulo; Daniel Sampaio Alves; Ewerton Yago de Sousa Rodrigues; Ray Silva de Almeida; Sheila Alves Gonçalves; Cícera Datiane de Morais Oliveira Tintino; Lucas Lopardi Franco; Ana Laura Marques Trinca; Douglas Henriques Novais; et al. (Folia Microbiologica, 2026)
Staphylococcus aureus is a Gram-positive coccus-type bacterium responsible for colonizing various sites of the host’s body, thus generating several pathologies such as pneumonia, osteomyelitis, endocarditis, and even cases of sepsis. Eugenol, dihydroeugenol, guaiacol, and phenol are phenolic compounds with antimicrobial activities, as is the drug metronidazole; therefore, eight substances were synthesized by coupling metronidazole with the molecules mentioned above, thus originating the compounds AD1–AD8. The present study aimed to evaluate the antibacterial activity and the capacity of the compounds AD1–AD8 to amplify the action of norfloxacin and ethidium bromide against the S . aureus 1199B strain through the inhibition of the NorA efflux pump. Broth microdilution assays were performed to determine the MIC and to analyze the association of the compounds AD1–AD8 with norfloxacin and ethidium bromide, along with the membrane permeability test and molecular docking. The compounds AD1–AD8 obtained positive results as they exhibited a potentiating effect by reducing the MIC of norfloxacin and ethidium bromide against 1199B, thus evidencing interference with the functioning of the NorA efflux pump, which had already been predicted by the data obtained from the molecular docking assay, in addition to having demonstrated significant effects by acting on the S. aureus membrane. The information obtained from this research is in line with what is reported in the literature regarding the effects observed with eugenol, dihydroeugenol, and guaiacol and their derivatives when combined with other antibiotics against S. aureus strains that possess efflux pumps, with competitive inhibition being observed, as well as the possibility that the reduction in MIC may have occurred due to a reduction in gene expression levels. Further assays are needed to evaluate these possibilities. Based on the presented data, it was found that the compounds AD1–AD8 exhibit promising aspects to act as antibiotic adjuvants.

IMTA Production of Pacific White Shrimp Integrated with Mullet, Sea Cucumber, Oyster, and Salicornia in a Biofloc System - Enrique A. Estévez Hernández; Ivanilson Santos; Laura Moraes; Morena Salala Kashane; Marcelo H. Okamoto; Luís André Sampaio; Dariano Krummenauer; César S. B. Costa; Ricardo V. Rodrigues; Silvia Martínez-Llorens; Luís H. Poersch (Fishes, 2026)
Integrated multitrophic aquaculture (IMTA) emerges as a sustainable strategy to control the excess of solids and inorganic nutrients that tend to increase in the biofloc system (BFT) cycle, since the model integrates organisms from different trophic levels sharing the same system and nutrients. Thus, this study compared a Penaeus vannamei monoculture system with an integrated biofloc system including Mugil liza, Holothuria grisea, Crassostrea tulipa, and Salicornia neei, focusing on water quality and the performance of organisms and systems. This study consisted of three monoculture systems (16 m3; 375 shrimp m−3) and three IMTA systems, composed of a shrimp tank (16 m3), a mullet tank (4 m3; 30 ind m−3), a combined tank (3 m3) for oysters (45 ind m−3) and sea cucumbers (3 ind m−2), and a Salicornia neei bed (2.78 m2; 37 ind m−2). All IMTA systems operated in recirculation without water exchange, using 10% of the established biofloc inoculum. The IMTA system had half the hydrated lime use (2.13 vs. 4.29 kg), lower solids (299.56 vs. 373.33 mg L−1), and reduced sludge production (9.37 vs. 15.87 kg). Shrimp growth was similar in both systems. Mullet grew adequately with a survival rate of 95.8%, but oysters showed a survival rate of 45.7%. Sea cucumber had a survival rate of 100% until day 28, when a marked decline appeared, strongly correlated with rising temperature (>28 °C; r = −0.71). This resulted in a significant increase in solids in the last weeks, suggesting that the population decline reduces solids control capacity. Furthermore, the biofloc in IMTA was dominated by coccoid forms, with lower proportions of filamentous and cyanobacterial forms.

Synchronous Miocene radiations and geographic-dependent diversification of pantropical Xylopia (Annonaceae) - Francis J. Nge; David M. Johnson; Nancy A. Murray; Laura Holzmeyer; Keegan Floyd; Gregory Stull; Vincent R.C. Soule; Pierre Sepulchre; Delphine Tardif; Carlos Rodrigues-Vaz; Thomas L.P. Couvreur (Molecular Phylogenetics and Evolution, 2026)

Red light–mediated enhancement of the antifungal activity of Physalis angulata against Candida species - Bianca Borges de Alencar; Maria Laura Faleiros Ribeiro de Melo; Wanderson Zuza Cosme; Matheus Henrique Francisco Dias; Camila Cristina Baccetti Medeiros; Rodrigo Sorrechia; Rosemeire Cristina Linhari Rodrigues Pietro; Fabiano Guimarães Silva; Marcio Luís Andrade e Silva; Wilson Roberto Cunha; Patrícia Mendonça Pauletti; Regina Helena Pires; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Effect of composition and processing method on physicochemical, structural, and rheological characteristics of milk and pea proteins hybrid gels - Lucas Silva de Sousa; Laura Destro Rodrigues; Davide Odelli; Raiane Rodrigues da Silva; Gustavo Schäfer Nogueira; Lucas Sales Queiroz; Paulo Peres de Sá Peixoto Junior; Antônio Fernandes de Carvalho (Food Research International, 2026)

Bioeconomic opportunities in restored tropical forests - Pedro Medrado Krainovic; João Paulo Romanelli; Angélica Faria de Resende; Laura Helena Porcari Simões; Ana Flávia Boeni; Lukas Rodrigues Souza; Cássio Augusto Patrocinio Toledo; Vinicius Castro Souza; Joannès Guillemot; Rens Brouwer; Frans Bongers; Paulo Guilherme Molin; et al. (Ambio, 2026)

The impact of land use and land cover on regulating ecosystem services provided by green infrastructures in Campinas, Brazil - Ana Laura Fragoso Favoreti; José Wellington Albuquerque; Bruno Noronha Rodrigues; Felippe Benavente Canteras; Vitor Eduardo Molina Junior (Environment, Development and Sustainability, 2026)
Over the past two decades, ecosystem services have gained recognition for their role in balancing ecosystems and human well-being. These encompass processes such as water purification, climate regulation, and pollination, which are often undervalued despite being critical for ecological balance and human health. Green infrastructure (GI) is especially recognized for its natural cooling effects, including shading and evapotranspiration, which help moderate local temperatures. This study investigates the role of GI in climate regulation in Campinas, Brazil, examining Land Use and Land Cover (LULC) changes and their impact on Land Surface Temperature (LST) using multi-temporal satellite data from 2018 to early 2024. Large-scale processing was conducted on a cloud-based geospatial platform (Google Earth Engine) to capture spatial–temporal patterns and improve analytical efficiency. Using remote sensing data, it evaluates vegetation indices and their correlation with LST across three zones: a densely urbanized area, a transitional agricultural zone, and a conservation forest. Findings indicate that areas near conservation forests exhibit significantly lower LST, whereas urban zones with reduced vegetation cover experience higher temperatures. The study demonstrates how GI effectively contributes to climate adaptation in tropical cities. This analysis identifies key spatial and temporal patterns that can inform sustainable urban planning. While noting limitations in spatial resolution, the study recommends integrating higher-resolution remote sensing and in situ data to enhance environmental analyses. These findings provide an evidence-based, replicable framework to guide urban planning and policy, promoting the protection and expansion of GI to mitigate urban heat and enhance climate resilience in tropical cities.

Plastic occurrence in Macaronesia: Three years of monitoring on forty-six beaches across nineteen islands in an Atlantic region - Cristopher Domínguez-Hernández; Cristina Villanova-Solano; Soledad Álvarez; Sergio J. Álvarez-Méndez; Adeline Alves; João Canning-Clode; Mara de Castro Abu-Raya; Francisco J. Díaz-Peña; Sofia Garcia; May Gómez; Javier González-Sálamo; Cintia Hernández-Sánchez; et al. (Science of The Total Environment, 2026)

Epididymal toxicity of deoxynivalenol: Age-specific effects in prepubertal and adult mice - Ana Laura Paulino Leite Gomes; Juliana Rubira Gerez; Marielen de Souza; Rafaela Pires Erthal; Dayane Priscila dos Santos; Camila Rodrigues Ferraz; Waldiceu A. Verri; Glaura Scantamburlo Alves Fernandes; Ana Paula Frederico Rodrigues Loureiro Bracarense (Reproductive Toxicology, 2026)

Alternative antimicrobials to Azidiol® for preserving raw milk samples for microbiological analysis - Rodrigo Antonio Pivatto; Franciele Rampazzo Vancin; Juarez Vicente; Laura Beatriz Rodrigues (International Dairy Journal, 2026)

Demographic Parameters of Iberian Killer Whales Between 2011 and 2023 - Ruth Esteban; Pauline Gauffier; Alfredo López; Francisco J. Gil‐Vera; Jörn Selling; Lilian Haristoy; Rocio Espada Ruiz; Pierre Guibert; André Días; Alfredo Rodrigues; Alejandro Onrubia; Mario Morcillo; et al. (Marine Mammal Science, 2026)
The Iberian killer whale subpopulation was assessed as critically endangered (CR) by the IUCN red list of threatened species based on the available information until 2011 on its low abundance, high newborn mortality, and dependency on the endangered Atlantic bluefin tuna. The present study focuses on updating the subpopulation demographic parameters between 2011 and 2023. Data were based on photo‐identification and stranding records. Abundance, survival, reproductive rates, and population growth were estimated through mark‐recapture models. Stranding records were used to estimate body size and calving seasonality. Sightings of newborn calves were also used for assessing seasonality. From 2011 through 2023, 26 stranding records were obtained, and 18,554 ID‐images were examined. This subpopulation showed a stable abundance, with 37 individuals in 2023, still qualifying for the IUCN CR category under criteria D. Calf survival rate has increased compared to pre‐2011, while adult survival has decreased, particularly for females. Reproductive rates were low, with an estimated interbirth interval of 8.3 years. The overall population growth rate was apparently stable at 0.46%. Most births occurred in the summer and fall. Iberian killer whales are generally smaller than the average body length of other killer whale populations throughout the world. The study emphasizes the need for long‐term monitoring and highlights new potential threats from fishing activities and recent disruptive interactions with recreational boats. The future of the subpopulation depends on recruitment and survival of juveniles and effective female reproduction.

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Antinociceptive, anti-inflammatory, and antioxidant effects of a flavonoid-rich phytocomplex from the leaves of Celtis iguanaea (jacq.) Sargent (Cannabaceae) - Dionys de Souza Almeida; Luiza Sousa Honorato; Lorrane Kelle da Silva Moreira; Larissa Córdova Turones; Rúbia Bellard e Silva; Mairon Cesar Coimbra; Laura Jéssica Pereira; Marx Osório Araújo Pereira; James Oluwagbamigbe Fajemiroye; José Realino de Paula; Júlio Onésio Ferreira Melo; José Luis Rodrigues Martins; et al. (Natural Product Research, 2025)

Phosphatidylserine translocation, cholesterol spatial distribution, and acrosome reaction reliably distinguish sperm capacitation from cryoinjury in bovine sperm - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues de Oliveira; Ellen Lara Miguel; Maíra Bianchi Rodrigues Alves; Raissa Braido Rangel; André Furugen Cesar de Andrade; Rubens Paes de Arruda; Karl Kerns; Eneiva Carla Carvalho Celeghini (Cryobiology, 2025)

Synbiotic administration improves systemic and vascular alterations in rats with experimental microsurgical extrahepatic cholestasis: role of perivascular mesenteric innervation - Pablo Méndez-Albiñana; Laia Cros-Brunsó; Raquel Rodrigues-Díez; Pilar Rodríguez-Rodríguez; Luis Santamaría; Ana Muñoz-Labrador; Teresa Requena; Laura Casani; Francisco Félix Caballero; Ma Isabel Prieto-Nieto; Mar Villamiel; Javier Blanco-Rivero (Bioactive Carbohydrates and Dietary Fibre, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Barcoding the Caatinga biome bees: a practical review - Pedro Rodrigues; Cláudia Teixeira; Laura Guimarães; Nuno G. C. Ferreira (Molecular Biology Reports, 2025)
Bees play a critical role as pollinators in ecosystem services, contributing significantly to the sexual reproduction and diversity of plants. The Caatinga biome in Brazil, home to around 200 bee species, provides an ideal habitat for these species due to its unique climate conditions. However, this biome faces threats from anthropogenic processes, making it urgent to characterise the local bee populations efficiently. Traditional taxonomic surveys for bee identification are complex due to the lack of suitable keys and expertise required. As a result, molecular barcoding has emerged as a valuable tool, using genome regions to compare and identify bee species. However, little is known about Caatinga bees to develop these molecular tools further. This study addresses this gap, providing an updated list of 262 Caatinga bee species across 86 genera and identifying ~ 40 primer sets to aid in barcoding these species. The findings highlight the ongoing work needed to fully characterise the Caatinga biome’s bee distribution and species or subspecies to support more effective monitoring and conservation efforts.

Yield and Fruit Quality of Grape Vines (Vitis labrusca L.) Under Distinct Training Systems in the Cerrado Mineiro, Campo Das Vertentes, Brazil - Paulo Márcio Norberto; Katiúcia Alves Amorim; Luíz Guilherme Malaquias da Silva; Maria Laura Silva Galdino; Geraldo de Sousa Candido; Carolina Valeriano de Carvalho; Filipe Almendagna Rodrigues; Angélica Bender (Applied Fruit Science, 2025)

Association of corn processing methods and sodium lasalocid for beef cattle on pasture during the finishing phase - Paloma Helena Gonçalves; Gabriel Santos Souza David; Laura Franco Prados; Bianca Rodrigues Domingos; Beatriz Lima Vellini; Felipe Almeida Nascimento; Willian Manoel Ricardo Foresto; Naiara Caixeta da Silva; Flávio Dutra de Resende; Gustavo Rezende Siqueira (Tropical Animal Health and Production, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Flood pulses reshape phytoplankton richness through aggregation, density, and species abundance distribution across floodplains - Laura A. Ortega-Corredor; Alfonso Pineda; Luzia Cleide Rodrigues (Science of The Total Environment, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

In silico search reveals the association of lichens with black yeast-like fungi in the order Chaetothyriales - Flavia de Fatima Costa; Bruno Paulo Rodrigues Lustosa; Camila Pereira Perico; Ricardo Belmonte-Lopes; João Lucas Vitório Ribeiro Carvalho; Emanuel L. Razzolini; Germana Davila dos Santos; Bruna Jacomel Favoreto de Souza Lima; Cristina Maria de Souza-Motta; Roberto Tadeu Raittz; Yinggai Song; Laura Selbmann; et al. (Fungal Biology, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Exploring Brucella spp. genomes for CRISPR-Cas systems - Leonardo Pereira de Araújo; Augusto Rodrigues Lima; Evandro Neves Silva; Thiago Caetano Andrade Belo; Laura Leone da Silva; Leonardo Augusto de Almeida; Patrícia Paiva Corsetti (Biologia, 2025)

Deoxynivalenol and male reproductive toxicity: Unraveling the hidden risks - Ana Laura Paulino Leite Gomes; Glaura Scantamburlo Alves Fernandes; Ana Paula Frederico Rodrigues Loureiro Bracarense (Toxicology, 2025)

Histological alterations in placentas of normal and anomalous pups: correlation with neonatal outcomes and fetal health - Laura M. Lovo; Marina Vilela Estevam; Samara Beretta; Amanda Marmol; Loren M. Pasqui; Fernanda A. Rodrigues-Silva; Renata O. Barreto; Alessandre Hataka; Gilson Hélio Toniollo; Maria Lúcia G. Lourenço; Maricy Apparício (Theriogenology, 2025)

Gestational success in a female dog following early repair of an inguinal gravid hysterocele - Gisele Almeida Lima da Veiga; Mariana Semião Francisco Talib; Marcelo Faustino; Roberto Rodrigues da Rosa Filho; Monike Alves Lopes; Guilherme Santos Souza; Laura Lima do Val Carneiro Machado; Camila Infantosi Vannucchi (Research in Veterinary Science, 2025)

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Voltage-gated Na+ channels: key players in the early tumorigenesis of breast cancer - Paula Rhana; Flávia Carvalho Aguiar; Diego Santos Souza; Ênio Ferreira Lima; Andréia Laura Prates Rodrigues; Jader Santos Cruz (Pflügers Archiv - European Journal of Physiology, 2025)

Soil bacteria and symbiotic rhizobia synergistically promote nitrogen fixation and biomass production of alfalfa (Medicago sativa L.) plants even under water shortage conditions without altering the native rhizospheric microbiota - Lisa Cangioli; Camilla Fagorzi; Francesca Vaccaro; Stefano Varriale; Maria Laura Amenta; Alessio Mengoni; Rosolino Ingraffia; Antonella Lo Porto; Gaetano Amato; Dario Giambalvo; Jean Rodrigue Sangaré; Roberto Defez; et al. (Applied Soil Ecology, 2025)

Impact of carbon footprint of food production on consumer perceptions and attitudes: Insights from text highlighting - Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Alexandre Henrique Silas Souza; Fabiana Borges Ribeiro; Taynara de Oliveira Ferreira; Laura Falavinha Vieira Bresciani; Jéssica Ferreira Rodrigues (Food Quality and Preference, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

How land use affects freshwater zooplankton communities: a global overview - Natan Guilherme Dos Santos; Laura Jardim Chiarelli; Pedro Henrique Ribeiro Morari; Maria Eduarda Turcato de Souza; Guilherme Calixto; Brendown Eiji Dias Kato; Gabriel Liboni Del Pino Rodrigues; Luana Cássia Figueira; Maria Stela Maioli Castilho-Noll (Hydrobiologia, 2025)

Deregulation of Neuroinflammatory and Neurotrophic Factors as Biological Events Triggered by D-Galactose Chronic Administration in Wistar Rats - Eduarda Behenck Medeiros; Sabrina da Silva; Francielle Mina; Adrielly Vargas Lidio; Amanda Boaventura; Laura Ceolin de Jesus; Michelle Lima Garcez; Gabriel Casagrande Zabot; Gabriela Piovesan Fenilli; Matheus Scarpatto Rodrigues; Jade de Oliveira; Samira S. Valvassori; et al. (NeuroMolecular Medicine, 2025)

Ayahuasca Pretreatment Prevents Sepsis-Induced Anxiety-Like Behavior, Neuroinflammation, and Oxidative Stress, and Increases Brain-Derived Neurotrophic Factor - Rick Wilhiam de Camargo; Larissa Joaquim; Richard Simon Machado; Suelen de Souza Ramos; Lara Rodrigues da Rosa; Linério Ribeiro de Novais Junior; Khiany Mathias; Lara Maximiano; Yasmin Ribeiro Strickert; Rafael Nord; Maria Laura Gava; Eduarda Scarpari; et al. (Molecular Neurobiology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

High‐Throughput Tn‐Seq Screens Identify Both Known and Novel Pseudomonas putida KT2440 Genes Involved in Metal Tolerance - Kevin Royet; Laura Kergoat; Stefanie Lutz; Charlotte Oriol; Nicolas Parisot; Christian Schori; Christian H. Ahrens; Agnes Rodrigue; Erwan Gueguen (Environmental Microbiology, 2025)
Industrial and urban activities release toxic chemical waste into the environment. Pseudomonas putida , a soil bacterium, is known to degrade hydrocarbons and xenobiotics, and possesses numerous genes associated with heavy metal tolerance. Most studies on metal tolerance in P. putida focus solely on over‐ or underexpressed genes, potentially overlooking important genes with unchanged expression. This study employed a Tn‐seq approach to identify the essential genes required for P. putida growth under metal stress. This method enables the identification of mutants with altered fitness in the presence of excess metals. The screen successfully identified a number of known genes implicated in metal resistance, including czcA‐1 , cadA‐3 , cadR , and pcoA2 , thereby validating the approach. Further analyses using targeted mutagenesis and complementation assays revealed PP_5337 as a putative transcriptional regulator involved in copper tolerance and the two‐component system RoxSR ( PP_0887/PP_0888 ) as a key determinant of cadmium tolerance. Additionally, PP_1663 and PP_5002 were identified as contributing to cadmium and cobalt tolerance, respectively. This study provides the first evidence linking these genes to metal tolerance, highlighting gaps in our understanding of metal tolerance mechanisms in P. putida and demonstrating the utility of Tn‐seq for identifying novel tolerance determinants.

Gibberellin biosynthesis inhibitors distinctly affect sunflower morphometric and growth dynamics - Carolina Ruv Lemes Gonçalves Mendes; Lusiane de Sousa Ferreira; Melina Rodrigues Alves Carnietto; Laura Costa Oliveira Almeida; Gustavo Ferreira da Silva; Hariane Luiz Santos; Carmen Sílvia Fernandes Boaro; Marcelo de Almeida Silva (South African Journal of Botany, 2025)

Are flash droughts intensifying in Brazil? - Javier Tomasella; Marcelo Zeri; Ana Paula Martins do Amaral Cunha; Roger Rodrigues Torres; Nancy Laura Rios Gamarra; Lidiane C. O. Costa (Climate Dynamics, 2025)

Method to Establish Intense Rainfall Equations Based in Geoprocessing - Laura Thebit de Almeida; Roberto Avelino Cecílio; Fernando Falco Pruski; Gerson Rodrigues dos Santos; Marcel Carvalho Abreu (Environmental Modeling & Assessment, 2025)

Warmer air temperatures predicted to result in wetland drying in the Upper Columbia River Valley, British Columbia, Canada - Italo Sampaio Rodrigues; Christopher Hopkinson; Laura Chasmer; Ryan J. MacDonald; Suzanne E. Bayley (Science of The Total Environment, 2025)

Efficiency of different techniques to analyze sperm capacitation in bulls - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues de Oliveira; Maíra Bianchi Rodrigues Alves; Juliano Coelho da Silveira; Felipe Perecin; Rubens Paes de Arruda; Eneiva Carla Carvalho Celeghini (Animal Reproduction Science, 2025)

Impact of climatic seasons on the dynamics of carbon, nitrogen and mercury in soils of Brazilian biomes affected by gold mining - Matheus B. Soares; Rebeca R. Rodrigues; Laura O. Péres; Carlos Eduardo P. Cerri; Luís Reynaldo F. Alleoni (Science of The Total Environment, 2024)

Flavonoids: the use in mental health and related diseases - Camilla Nicolucci; Milena Padovani; Fernanda de Castro Rodrigues; Laura Nagy Fritsch; Ana Cristina Santos; Denise Gonçalves Priolli; Juliana M. Sciani (Natural Product Research, 2024)

Correction: Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Evaluation of the effects of the Zika Virus-Immunoglobulin G+ complex on murine microglial cells - Laura da Silva Siqueira; Felipe Valle Fortes Rodrigues; Ângela Zanatta; João Ismael Budelon Gonçalves; Isadora Machado Ghilardi; Allan Marinho Alcará; Nicole Bernd Becker; Giulia Pinzetta; Gabriele Zanirati; Bruno Maestri Abrianos Becker; Helena Scartassini Erwig; Jaderson Costa da Costa; et al. (Journal of NeuroVirology, 2024)

Light spectra on in vitro seed germination of the Brazilian cactus Cereus jamacaru DC. subsp. jamacaru - Marina Barros Zacharias; Laura Minatel Bortolato; Guilherme Bovi Ambrosano; Paulo Hercílio Viegas Rodrigues (Vegetos, 2024)

Corrigendum to “Aqueous PM2.5 promotes lipid accumulation, classical macrophage polarisation and heat shock response” [Chemosphere 363 (2024)] - Lílian Corrêa Costa-Beber; Rafael Kazmirczak Moraes; Jéssica Marques Obelar Ramos; Leo Anderson Meira Martins; Ana Laura Toquetto; Júlia Fursel Pacheco; Hémelin Resende Farias; Adriana Gioda; Vitor Antunes de Oliveira; Jade de Oliveira; Fatima Theresinha Costa Rodrigues Guma (Chemosphere, 2024)

Aqueous PM2.5 promotes lipid accumulation, classical macrophage polarisation and heat shock response - Lílian Corrêa Costa-Beber; Rafael Kazmirczak Moraes; Jéssica Marques Obelar Ramos; Leo Anderson Meira Martins; Ana Laura Toquetto; Júlia Fursel Pacheco; Hémelin Resende Farias; Adriana Gioda; Vitor Antunes de Oliveira; Jade de Oliveira; Fátima Theresinha Costa Rodrigues Guma (Chemosphere, 2024)

An assessment on the effects of buffers on the productive, behavioral and metabolic parameters of Holstein dairy cows - Laura Valadão Vieira; Magna Fabrícia Brasil Savela; Natália Machado Rahal; Antônio Amaral Barbosa; Diego Rodrigues Saraiva; Francisco Augusto Burkert Del Pino; Viviane Rohrig Rabassa; Eliza Rossi Komninou; Cássio Cassal Brauner; Diego Langwinski; Alexandre Souza; Marcio Nunes Corrêa (Tropical Animal Health and Production, 2024)

Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

A longer period of epididymal sperm interaction with extender components during cryopreservation improves sperm quality, decreases the size of sperm distal cytoplasmic droplets, and changes the number of nanoparticles in the extender - Maria Alice de Almeida; Laura Gabrielli Haupenthal; Amanda Nespolo Silva; Gabriela Melendes Schneider; Paola Maria da Silva Rosa; André Furugen César de Andrade; Luciano Andrade Silva; Flávio Vieira Meirelles; Juliano Coelho da Silveira; Felipe Perecin; Maíra Bianchi Rodrigues Alves (Cryobiology, 2024)

Encapsulation of hydrophobic active ingredients in plant proteins: modulation of interfacial properties and encapsulation efficiency - Janaína G Fernandes; Ramila C Rodrigues; Laura Pereira; Paulo C Stringheta; Pedro H Campelo; Evandro Martins (Current Opinion in Food Science, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Bioaccumulation of metals in Spartina alterniflora salt marshes in the estuary of the World’s Largest Choked Lagoon - Laura Lemons Moreira; Ronan Adler Tavella; Alicia da Silva Bonifácio; Rodrigo de Lima Brum; Livia da Silva Freitas; Niely Galeão da Rosa Moraes; Maria Laura Fiasconaro; Paula Florencio Ramires; Julia Oliveira Penteado; Paulo Roberto Martins Baisch; Flavio Manoel Rodrigues da Silva Júnior (Environmental Science and Pollution Research, 2024)

Role of vulvovaginal candidiasis infection in infertility: systematic review and meta-analysis - Ana Luiza P. Córdova; Stéfani Z. M. Fontanella; Tamy Colonetti; Maria Laura Rodrigues Uggioni; Antonio José Grande; Maria Carolina Saggioratto; Eduardo Schmitt Testoni; Maria Inês Rosa (Brazilian Journal of Microbiology, 2024)

Polystyrene nanoplastics induce developmental impairments and vasotoxicity in zebrafish (Danio rerio) - Andressa Liberal Santos; Laura Carvalho Rodrigues; Cândido Carvalho Rodrigues; Felipe Cirqueira; Guilherme Malafaia; Thiago Lopes Rocha (Journal of Hazardous Materials, 2024)

Genetic diversity of adenovirus in neotropical bats from Brazil - Laís Santos Rizotto; Larissa Mayumi Bueno; Thaís Camilo Corrêa; Maria Vitória dos Santos de Moraes; Amanda de Oliveira Viana; Laura Morais Nascimento Silva; Julia Cristina Benassi; Guilherme Pereira Scagion; Bruna Larotonda Telezynski Lopes; Isabela Barbosa de Assis; Tatiana Ometto; Erick Gustavo Dorlass; et al. (Brazilian Journal of Microbiology, 2023)

Predicting the distribution and abundance of abandoned, lost or discarded fishing gear (ALDFG) in the deep sea of the Azores (North Atlantic) - Emily M. Duncan; Nina Vieira; José Manuel González-Irusta; Carlos Dominguez-Carrió; Telmo Morato; Marina Carreiro-Silva; Joachim Jakobsen; Kirsten Jakobsen; Filipe Porteiro; Nina Schläpfer; Laura Herrera; Manuela Ramos; et al. (Science of The Total Environment, 2023)

Influence of spontaneous and inoculated fermentation of açai on simulated digestion, antioxidant capacity and cytotoxic activity - Amanda Lais Alves Almeida Nascimento; Mariane Sampaio da Silveira de Souza; Larissa Lorrane Rodrigues Borges; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Adriana Correa Mendonça; Luciana Azevedo; Mariana Araújo Vieira do Carmo; Amanda dos Santos Lima; Laura da Silva Cruz; Gabriel Abranches Dias Castro; Sergio Antonio Fernandes; et al. (Food Research International, 2023)

Characterization of Depression- and Anxiety-Like Behaviours in a Mouse Model of Relapsing-Remitting Multiple Sclerosis - Diulle Spat Peres; Fernanda Tibolla Viero; Patrícia Rodrigues; Laura de Barros Bernardes; Náthaly Andriguetto Ruviaro da Silva; Igor Ramos Lima; Gabrielli Martins; Paulo Cesar Lock Silveira; Marcella de Amorim Ferreira; Ana Merian Silva; Juliano Ferreira; Gabriela Trevisan (Journal of Neuroimmune Pharmacology, 2023)

Topical formulations containing Trichilia catigua extract as therapeutic options for a genital and an acyclovir-resistant strain of herpes recurrent infection - Elisa Vicente Ribelato; Jéssica Wouk; Gabriela Gomes Celestino; Bianca Cerqueira Dias Rodrigues; Maria Laura Goussain Darido; Mario Gabriel Lopes Barboza; Tatiana Jabor Botura; Maylla Cardoso de Oliveira; Fábio Goulart de Andrade; Audrey A. S. G. Lonni; João Carlos Palazzo de Mello; Sérgio Paulo Dejato da Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Welfare assessment of horses and mules used in commercial beef cattle ranches in Brazil - Laura Zuliani; Pedro Henrique Esteves Trindade; Mateus José Rodrigues Paranhos da Costa (Applied Animal Behaviour Science, 2023)

Correction to: Substitution of petrochemical compounds for polyphenols of natural origin reinforced with cellulose nanofibrils to formulate adhesives for wood bonding - Uasmim Lira Zidanes; Mário Sérgio Lorenço; Elesandra da Silva Araujo; Matheus Cordazzo Dias; Laura Luiza Amaral Rodrigues; Bruno Arley Barros Dores; Carine Setter; José Benedito Guimarães Júnior; Gustavo Henrique Denzin Tonoli; Fábio Akira Mori (Environmental Science and Pollution Research, 2023)

Myeloperoxidase enzyme and Ferric-reducing antioxidant power concentrations in lean and obese dogs - Rodrigo Rodrigues Paulo; Victoria Elizabeth Galvão; Gustavo Gomes da Silva; Laura Pereira Porto; Juliana Mayumi Tonossu; Maira Beatriz Gandolfi; Priscylla Tatiana Chalfun Guimarães-Okamoto; Regina Kiomi Takahira; Sheila Canevese Rahal; Alessandra Melchert (Veterinary Research Communications, 2023)

Landslide susceptibility zonation using the analytical hierarchy process (AHP) in the Bafoussam-Dschang region (West Cameroon) - Flavie Laura Zangmene; Moussa Nsangou Ngapna; Moïse Christian Balla Ateba; Germain Marie Monespérance Mboudou; Pascal Landry Wabo Defo; Rodrigue Tetang Kouo; Armand Kagou Dongmo; Sébastien Owona (Advances in Space Research, 2023)

The impact of Brazilian coast oil spill on the mesozooplankton of the tropical narrowest continental shelf - Christiane Sampaio De Souza; Paulo De Oliveira Mafalda Junior; Laura Rodrigues Da Conceição; Ruy Kenji Papa De Kikuchi; José Maria Landim Dominguez (Aquatic Ecology, 2023)

Substitution of petrochemical compounds for polyphenols of natural origin reinforced with cellulose nanofibrils to formulate adhesives for wood bonding - Uasmim Lira Zidanes; Mário Sérgio Lorenço; Elesandra da Silva Araujo; Matheus Cordazzo Dias; Laura Luiza Amaral Rodrigues; Bruno Arley Barros Dores; Carine Setter; José Benedito Guimarães Júnior; Gustavo Henrique Denzin Tonoli; Fábio Akira Mori (Environmental Science and Pollution Research, 2023)

Controlled lipid self-assembly for scalable manufacturing of next-generation immune stimulating complexes - Ivan S. Pires; Kaiyuan Ni; Mariane Bandeira Melo; Na Li; Elana Ben-Akiva; Laura Maiorino; Jonathan Dye; Kristen A. Rodrigues; DongSoo Yun; Byungji Kim; Ryan R. Hosn; Paula T. Hammond; et al. (Chemical Engineering Journal, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Distribution and antifungal susceptibility profiles of Candida species isolated from people living with HIV/AIDS in a public hospital in Goiânia, GO, Brazil - Vivianny Aparecida Queiroz Freitas; Andressa Santana Santos; Ana Laura Sene Amâncio Zara; Carolina Rodrigues Costa; Cassia Silva de Miranda Godoy; Renata de Bastos Ascenço Soares; Fábio Silvestre Ataídes; Maria do Rosário Rodrigues Silva (Brazilian Journal of Microbiology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Use of maltodextrin, sweet potato flour, pectin and gelatin as wall material for microencapsulating Lactiplantibacillus plantarum by spray drying: Thermal resistance, in vitro release behavior, storage stability and physicochemical properties - Nataly de Almeida Costa; Laura Rodrigues Silveira; Ester de Paula Amaral; Gabriel Clementino Pereira; Daniele de Almeida Paula; Érica Nascif Rufino Vieira; Eliane Maurício Furtado Martins; Paulo César Stringheta; Bruno Ricardo de Castro Leite Júnior; Afonso Mota Ramos (Food Research International, 2023)

Multiple exposure pathways and health risk assessment of potentially harmful elements for children and adults living in a coal region in Brazil - Paula Florencio Ramires; Marina dos Santos; Soraya Paz-Montelongo; Carmen Rubio-Armendáriz; Diana Adamatti; Maria Laura Fiasconaro; Flávio Manoel Rodrigues da Silva Júnior (Environmental Geochemistry and Health, 2023)

Graded concentrations of lidocaine hydrochloride in the modulation of behavioral, cardiac, and muscular responses of the Amazon freshwater fish tambaqui (Colossoma macropomum) - Luana Rodrigues Vieira; Yago Luiz Gonçalves Pereira; Laura Andrade Diniz; Chirlene Pinheiro Nascimento; Alex Luiz Mendesda Silva; Julianne Elba Cunha Azevedo; Vanessa Jóia de Mello; Nilton Akio Muto; Luis André Luz Barbas; Moisés Hamoy (Aquaculture, 2023)

Nutrients and not temperature are the key drivers for cyanobacterial biomass in the Americas - Sylvia Bonilla; Anabella Aguilera; Luis Aubriot; Vera Huszar; Viviana Almanza; Signe Haakonsson; Irina Izaguirre; Inés O'Farrell; Anthony Salazar; Vanessa Becker; Bruno Cremella; Carla Ferragut; et al. (Harmful Algae, 2023)

Different Multidrug-Resistant Salmonella spp. Serovars Isolated from Slaughter Calves in Southern Brazil - Alex Dall Agnol Gabana; Adriana Souto Pereira Núncio; Bruna Correa Lopes; Júlia Alves de Oliveira; Luana da Silva Monteiro; Mario de Menezes Coppola; Thales Quedi Furian; Karen Apellanis Borges; Laura Beatriz Rodrigues; Fabiana Quoos Mayer (Current Microbiology, 2023)

Oral Medicine Experience and Attitudes Toward Oral Cancer: An Evaluation of Dentists Working in Primary Health Care - Jéssica Rodriguez Strey; Michelle Roxo-Gonçalves; Bianca Dutra Guzenski; Marco Antonio Trevizani Martins; Juliana Romanini; Maria Antonia Zancanaro de Figueiredo; Otávio Pereira D’Ávila; Marcelo Rodrigues Gonçalves; Roberto Nunes Umpierre; Erno Harzheim; Laura de Campos Hildebrand; Vinicius Coelho Carrard (Journal of Cancer Education, 2022)

SARS-CoV-2 Omicron BA.1, BA.2, and XAG identification during routine surveillance on a university campus in Belo Horizonte, Brazil, 2022 - Daniel Costa Queiroz; Natália Virtude Carobin; Luiza Campos Guerra de Araújo e Santos; Paula Luize Camargos Fonseca; Isabela Lorraine Braga-Paz; Rillery Calixto Dias; Jorge Gomes Goulart Ferreira; Túlio Resende Freitas; Diego Menezes; Sílvia Cristina Verde Mendes Nolasco; Simone Rodrigues Ribeiro; Thaís Salviana Ribeiro; et al. (Brazilian Journal of Microbiology, 2022)

Analysis of Flow Behavior as Influenced by Reservoir with Flow Regularization - Tarcila Neves Generoso; Demetrius David da Silva; Lineu Neiva Rodrigues; Ricardo Santos Silva Amorim; Laura Thebit de Almeida (Water Resources Management, 2022)

Amphistegina lobifera foraminifera are excellent bioindicators of heat stress on high latitude Red Sea reefs - Alexander F. Humphreys; Ameer Abdulla; Sofia Sherman; Jaclyn Levine; Katelyn Arista; Laura Jones; Charlotte Hoffman; Giacomo Palavicini; Silvia Vimercati; Tullia I. Terraneo; Mustapha Ouhssain; Mattie Rodrigue; et al. (Coral Reefs, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Understanding Fish Larvae’s Feeding Biology to Improve Aquaculture Feeding Protocols - Laura Ribeiro; François Noel Hubert; Vera Rodrigues; Carlos Rojas-Garcia; Maria Teresa Dinis (Oceans, 2022)
Knowing that food ingestion and digestion are processes under neuroendocrine regulation, it is important to understand how fish larvae regulate these processes, when the digestive system itself is under development. This study aimed to analyze how gilthead seabream (Sparus aurata) larval feeding incidence and intensity were affected by time, light, and water temperature, through the analysis of gut content and how this affected cholecystokinin (CCK) content. Three short-term experiments were done: (A) 27 and 42 days post-hatch (DPH) larvae were analyzed at different intervals for 80 min, after feeding; (B) 38 and 48 DPH larvae were kept under different light intensities (0, 400, 1000 lux) for 30 min; (C) 41 DPH larvae were kept at 17, 19, 25 °C for 30 min. Feeding incidence below 100% was observed for 27 DPH larvae, and for 38 DPH larvae fed at 0 lux. Feeding intensity was several fold higher at older ages. However, the number of prey in the gut was lower at 0 lux, and higher at 25 °C. Overall, no clear pattern was observed for CCK, but at older ages increasing gut content resulted in higher CCK content. In conclusion, until 38 DPH light is important for gilthead sea bream larval feeding ability, and maturing functionality of CCK was only observed at later stages.

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

Differential use of trophic resources between an exotic and a coexisting native snail - Paula Altieri; Laura Estefanía Paz; Ana Clara Ferreira; Karine Delevati Colpo; Alberto Rodrigues Capítulo; Roberto Jensen; Vladimir Costa; Carolina Ocon (Limnology, 2022)

Dietary tryptophan supplementation does not affect growth but increases brain serotonin level and modulates the expression of some liver genes in zebrafish (Danio rerio) - Cláudia Teixeira; Pedro Rodrigues; Paula Serrão; Luís Figueira; Laura Guimarães; Luís Oliva Teles; Helena Peres; António Paulo Carvalho (Fish Physiology and Biochemistry, 2021)

Ecotoxicity of triclosan in soil: an approach using different species - Paula Florêncio Ramires; Ronan Adler Tavella; Ana Laura Escarrone; Lisiane Martins Volcão; Laiz Coutelle Honscha; Rodrigo de Lima Brum; Alícia Bonifácio da Silva; Flávio Manoel Rodrigues da Silva Júnior (Environmental Science and Pollution Research, 2021)

Pesticide and trace element bioaccumulation in wild owls in Brazil - Gabriela Elisa Dal Pizzol; Vitória Aquino Rosano; Elinton Rezende; Jonas Claudiomar Kilpp; Marcelo Menezes Ferretto; Enzo Mistura; Arthur Nery da Silva; Charise Dallazem Bertol; Laura Beatriz Rodrigues; Maria Tereza Friedrich; Luciana Grazziotin Rossato-Grando (Environmental Science and Pollution Research, 2021)

Performance of broiler chicken submitted to a quantitative feed restriction program - Tiago Bordin; Fernando Pilotto; Daniela Pesenatto; Bruno Sebastião de Mendonça; Luciane Daroit; Laura Beatriz Rodrigues; Ezequiel Davi dos Santos; Elci Lotar Dickel (Tropical Animal Health and Production, 2021)

Punicalagin triggers ergosterol biosynthesis disruption and cell cycle arrest in Cryptococcus gattii and Candida albicans - Thaísa Cristina Silva; Renato Ivan de Ávila; Ana Laura Sene Amâncio Zara; Andressa Santana Santos; Fábio Ataídes; Vivianny Aparecida Queiroz Freitas; Carolina Rodrigues Costa; Marize Campos Valadares; Maria do Rosário Rodrigues Silva (Brazilian Journal of Microbiology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Damming reduced the functional richness and caused the shift to a new functional state of the phytoplankton in a subtropical region - Alfonso Pineda; Patrícia Iatskiu; Susicley Jati; Aline C. M. Paula; Bárbara F. Zanco; Claudia C. Bonecker; Geovani A. Moresco; Laura A. Ortega; Yasmin R. Souza; Luzia C. Rodrigues (Hydrobiologia, 2020)

Sugarcane Juice with Co-encapsulated Bifidobacterium animalis subsp. lactis BLC1 and Proanthocyanidin-Rich Cinnamon Extract - Augusto Tasch Holkem; Edmur José Santos Neto; Megumi Nakayama; Clitor J. F. Souza; Marcelo Thomazini; Fabio Augusto Gallo; Marluci Palazzolli da Silva; Laura de Queiroz Bomdespacho; Carla Giovana Luciano; Izabel Cristina Freitas Moraes; Rodrigo Rodrigues Petrus; Carmen S. Favaro-Trindade (Probiotics and Antimicrobial Proteins, 2020)

Heat stress effects on bovine sperm cells: a chronological approach to early findings - Laura Nataly Garcia-Oliveros; Rubens Paes de Arruda; Leonardo Batissaco; Vitor Hugo Guilger Gonzaga; Vinícius José Moreira Nogueira; Shirley Andrea Florez-Rodriguez; Flávia dos Santos Almeida; Maíra Bianchi Rodrigues Alves; Sâmara Cristine Costa Pinto; Marcilio Nichi; João Diego de Agostini Losano; Giulia Kiyomi Vechiato Kawai; et al. (International Journal of Biometeorology, 2020)

Antimicrobial and Disinfectant Susceptibility of Salmonella Serotypes Isolated from Swine Slaughterhouses - Caroline L. de Quadros; Luciane Manto; Enzo Mistura; Bruna Webber; Giseli A. Ritterbusch; Karen A. Borges; Thales Q. Furian; Laura B. Rodrigues; Luciana R. dos Santos (Current Microbiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Exercise Modalities Improve Aversive Memory and Survival Rate in Aged Rats: Role of Hippocampal Epigenetic Modifications - Louisiana Carolina Ferreira de Meireles; Fernando Galvão; Deena M. Walker; Laura Reck Cechinel; Ágnis Iohana de Souza Grefenhagen; Gisele Andrade; Roberta Passos Palazzo; Gisele Agustini Lovatel; Carla Giovanna Basso; Eric J. Nestler; Ionara Rodrigues Siqueira (Molecular Neurobiology, 2019)

Development and characterization of 19 polymorphic microsatellite loci from the Red-cowled Cardinal (Paroaria dominicana, Passeriformes, Aves) using next-generation sequencing - Ana Laura Rosa; Cássia Alves Lima-Rezende; Fernando Pacheco Rodrigues; Renato Caparroz (Molecular Biology Reports, 2019)

Assessing the ecological status of small Mediterranean rivers using benthic macroinvertebrates and macrophytes as indicators - Carolina Rodrigues; Paulo Alves; Ana Bio; Cristiana Vieira; Laura Guimarães; Carlos Pinheiro; Natividade Vieira (Environmental Monitoring and Assessment, 2019)

Reduced Rainfall Increases Metabolic Rates in Upper Mixed Layers of Tropical Lakes - Laura Martins Gagliardi; Ludmila Silva Brighenti; Peter Anton Staehr; Francisco Antônio Rodrigues Barbosa; José Fernandes Bezerra-Neto (Ecosystems, 2019)

Combining biomarker and community approaches using benthic macroinvertebrates can improve the assessment of the ecological status of rivers - Carolina Rodrigues; Laura Guimarães; Natividade Vieira (Hydrobiologia, 2019)

Assessing the ecological status of fluvial ecosystems employing a macroinvertebrate multi-taxon and multi-biomarker approach - Carolina Rodrigues; Ana Bio; Laura Guimarães; Virgínia C. Fernandes; Cristina Delerue-Matos; Natividade Vieira (Environmental Monitoring and Assessment, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Circulating extracellular vesicles in the aging process: impact of aerobic exercise - Karine Bertoldi; Laura Reck Cechinel; Bruna Schallenberger; Giana Blume Corssac; Samuel Davies; Irene Clemes Külkamp Guerreiro; Adriane Belló-Klein; Alex Sander R. Araujo; Ionara Rodrigues Siqueira (Molecular and Cellular Biochemistry, 2018)

N-acylhydrazones containing thiophene nucleus: a new anticancer class - Laura N. F. Cardoso; Thais C. M. Nogueira; Felipe A. R. Rodrigues; Augusto Cesar Aragão Oliveira; Maria Claudia dos Santos Luciano; Claudia Pessoa; Marcus V. N. de Souza (Medicinal Chemistry Research, 2017)

Effect of tannery effluent on oxidative status of brain structures and liver of rodents - Felipe dos Santos Moysés; Karine Bertoldi; Viviane Rostirola Elsner; Laura Reck Cechinel; Carla Basso; Simone Stülp; Marco Antônio Siqueira Rodrigues; Ionara Rodrigues Siqueira (Environmental Science and Pollution Research, 2017)

Reassessment of the taxonomic position of Burkholderia andropogonis and description of Robbsia andropogonis gen. nov., comb. nov. - Lucilene Lopes-Santos; Daniel Bedo Assumpção Castro; Mariana Ferreira-Tonin; Daniele Bussioli Alves Corrêa; Bevan Simon Weir; Duckchul Park; Laura Maria Mariscal Ottoboni; Júlio Rodrigues Neto; Suzete Aparecida Lanza Destéfano (Antonie van Leeuwenhoek, 2017)

Oxidative Stress, Disrupted Energy Metabolism, and Altered Signaling Pathways in Glutaryl-CoA Dehydrogenase Knockout Mice: Potential Implications of Quinolinic Acid Toxicity in the Neuropathology of Glutaric Acidemia Type I - Bianca Seminotti; Alexandre Umpierrez Amaral; Rafael Teixeira Ribeiro; Marília Danyelle Nunes Rodrigues; Ana Laura Colín-González; Guilhian Leipnitz; Abel Santamaría; Moacir Wajner (Molecular Neurobiology, 2016)

Induction of a Proinflammatory Response in Cortical Astrocytes by the Major Metabolites Accumulating in HMG-CoA Lyase Deficiency: the Role of ERK Signaling Pathway in Cytokine Release - Carolina Gonçalves Fernandes; Marília Danyelle Nunes Rodrigues; Bianca Seminotti; Ana Laura Colín-González; Abel Santamaria; André Quincozes-Santos; Moacir Wajner (Molecular Neurobiology, 2016)

Seasonal Changes in Metabolic Rates of Two Tropical Lakes in the Atlantic Forest of Brazil - Ludmila Silva Brighenti; Peter Anton Staehr; Laura Martins Gagliardi; Luciana Pena Mello Brandão; Eliane Côrrea Elias; Nelson Azevedo Santos Teixeira de Mello; Francisco Antônio Rodrigues Barbosa; José Fernandes Bezerra-Neto (Ecosystems, 2015)

Bacterial diversity assessment in soil of an active Brazilian copper mine using high-throughput sequencing of 16S rDNA amplicons - Viviane D. Rodrigues; Tatiana T. Torres; Laura M. M. Ottoboni (Antonie van Leeuwenhoek, 2014)

Do wood-based panels made with agro-industrial residues provide environmentally benign alternatives? An LCA case study of sugarcane bagasse addition to particle board manufacturing - Diogo Aparecido Lopes Silva; Francisco Antonio Rocco Lahr; Ana Laura Raymundo Pavan; Yovana M. B. Saavedra; Natalia Crespo Mendes; Sabrina Rodrigues Sousa; Roberta Sanches; Aldo Roberto Ometto (The International Journal of Life Cycle Assessment, 2014)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Effects of salinity stress on neurotransmission, energy metabolism, and anti-oxidant biomarkers of Carcinus maenas from two estuaries of the NW Iberian Peninsula - Aurélie Pinto Rodrigues; Patrícia Correia Oliveira; Lúcia Guilhermino; Laura Guimarães (Marine Biology, 2012)

Pattern of asthma medication use among children from a large urban center in Brazil - Djanilson Barbosa Santos; Alvaro A. Cruz; Silvia de Magalhães Simões; Laura C. Rodrigues; Paulo Augusto Moreira Camargos; Helena Lutescia Luna Coelho; Mauricio L. Barreto (European Journal of Clinical Pharmacology, 2012)

Relationships between the spatial distribution of oligochaetes (Annelida, Clitellata) and environmental variables in a temperate estuary system of South America (Río de la Plata, Argentina) - Laura Cecilia Armendáriz; Alberto Rodrigues Capítulo; Eugenia Soledad Ambrosio (New Zealand Journal of Marine and Freshwater Research, 2011)
The oligochaete assemblage on the Argentine coast of the Río de la Plata estuary was sampled seasonally within environments having different types of disturbances. Three habitats were sampled: sediments free of vegetation, sediments within bullrush stands and substrates with Limnoperna fortunei . The species richness, evenness and Shannon–Wiener diversity values were different among those habitats. The only dominant species (according to the Kownacki index) was Nais variabilis . Mean density values varied between 400 and 199,500 ind./m 2 . Organic matter, ammonium and phosphates correlated positively with the mean oligochaete abundance, but not with the granulometry. Physicochemical variables and nutrient levels were measured and their relation to the sampling sites assessed through a principal component analysis (41.8% cumulative variance). The canonical correspondence analysis (41.2% cumulative variance) indicated that the oligochaetes distributed along both a eutrophication–pollution gradient and a turbidity–conductivity gradient. These results would be useful for assessing the ecological status of estuaries for a subsequent implementation of appropriate sustainability‐management policies.

Manayunkia speciosa Leidy (Polychaeta: Sabellidae): introduction of this nonindigenous species in the Neotropical Region (Uruguay river, South America) - Laura C. Armendáriz; Analía Paola; Alberto Rodrigues Capítulo (Biological Invasions, 2011)

Multiple Pathways Analysis of Brain Functional Networks from EEG Signals: An Application to Real Data - Fabrizio De Vico Fallani; Francisco Aparecido Rodrigues; Luciano da Fontoura Costa; Laura Astolfi; Febo Cincotti; Donatella Mattia; Serenella Salinari; Fabio Babiloni (Brain Topography, 2011)

Lack of essential fatty acids in live feed during larval and post-larval rearing: effect on the performance of juvenile Solea senegalensis - Maria Luísa Dâmaso-Rodrigues; Pedro Pousão-Ferreira; Laura Ribeiro; Joana Coutinho; Narcisa M. Bandarra; Paulo J. Gavaia; Luís Narciso; Sofia Morais (Aquaculture International, 2010)

Identification of predator–prey relationships between coccinellids and Saissetia oleae (Hemiptera: Coccidae), in olive groves, using an enzyme-linked immunosorbent assay - Sónia A. P. Santos; José A. Pereira; Maria da Conceição Rodrigues; Laura M. Torres; Ana Maria N. Pereira; António J. A. Nogueira (Journal of Pest Science, 2009)

Variation in articular cartilage in rats between 3 and 32 months old. A histomorphometric and scanning electron microscopy study - Juliano Yasuo Oda; Edson Aparecido Liberti; Laura Beatriz Mesiano Maifrino; Romeu Rodrigues de Souza (Biogerontology, 2007)

GENEHUNTER versus SimWalk2 in the context of an extended kindred and a qualitative trait locus - Sandra Romero-Hidalgo; Eliane R. Rodrigues; Eduardo Gutirrez-Pea; Laura Riba; Mara Teresa Tusi-Luna (Genetica, 2005)